A Perfect Nicking Pattern - Nash, Richard (Humanimalia, 2021)
The ideological underpinnings of the Early Modern practice of animal breeding that brought into being the animal now designated as the thoroughbred horse are explored here by attending to the terminology and original meaning of a breeding theory that persists even in contemporary practice, albeit in a dramatically altered form from its eighteenth-century origins. A significant component of today’s multi-billion dollar commercial breeding industry is a tool of analysis known as attention to “nicking patterns” — patterns that inform decisions about managed breeding of stallions and mares. Moving quickly beyond a brief discussion of how nicking patterns function today to locate the origin of this theory in Early Modern Animal Breeding practice; the discussion proceeds to illustrate how this practice keeps in play a series of underlying tensions that operate as powerfully in our current era as in the age in which the thoroughbred arose.